2013
DOI: 10.7314/apjcp.2013.14.1.255
|View full text |Cite
|
Sign up to set email alerts
|

Living Experiences of Male Spouses of Patients with Metastatic Cancer in Taiwan

Abstract: Background: Cancer is the leading cause of death in Taiwan. Spouses are generally the main caregivers of affectyed patients but previous studies have seldom investigated the needs of male spouses of patients with metastatic cancer. Purpose: To explore the lived experiences of such male spouses. Methods: A qualitative design using in-depth interviewswasconducted with male spouses of patients with metastatic cancer being treated at the oncology outpatient department in a teaching hospital in northern Taiwan. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Frankowska and Wiechula () found that study participants hesitated to disclose their caregiving role to others, because metaphorically this indicated they had “lost a partner.” By contrast, caregivers who identified themselves as partners, and as a couple, in both their private lives and with health care professionals, were strengthened by this bond and developed a more positive self‐concept (Donnelly, ; Galvin et al, ; Greenwood, Mackenzie, Wilson, & Cloud, ; Harrow et al, ; Liedstrom, Isaksson, & Ahlstrom, ; Lin, Lin, Lee, & Lin, ; Sadala, Stolf, Bocchi, & Bicudo, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Frankowska and Wiechula () found that study participants hesitated to disclose their caregiving role to others, because metaphorically this indicated they had “lost a partner.” By contrast, caregivers who identified themselves as partners, and as a couple, in both their private lives and with health care professionals, were strengthened by this bond and developed a more positive self‐concept (Donnelly, ; Galvin et al, ; Greenwood, Mackenzie, Wilson, & Cloud, ; Harrow et al, ; Liedstrom, Isaksson, & Ahlstrom, ; Lin, Lin, Lee, & Lin, ; Sadala, Stolf, Bocchi, & Bicudo, ).…”
Section: Resultsmentioning
confidence: 99%
“…The theme of uncertainty was present in almost every report, as caregivers associated this time with feeling they had no clear future and being unable to plan ahead (Adams, ; Burman, ; Frankowska & Wiechula, ; Galvin et al, ; Huang & Peng, ; Lin et al, ; Murray et al, ; Plank et al, ; Stone & Jones, ). This uncertainty stemmed from their perceptions of the care recipient's health status, including the illness trajectory as well as prognosis (e.g., risk of death).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations